La coopetencia, interacción de dos relaciones antagónicas - Gómez Díaz, Javier; García Garnica, Alejandro; Curiel Aviles, Urbano Gustavo (Dimensión Empresarial, 2018)
Businesses are developed in highly dynamic environments, so companies seek access to resources that allow them to cope with variations. One of these strategies is cooperation in which companies cooperate and compete towards a common goal. In the cooperative, companies that compete and cooperate looking for a common goal. Through sharing (cooperation) the resources create value, the appropriation of this value is derived from the various interests (competition) of the companies, catches the value created for their purposes.
Coopetencia, interaction of two antagonist relations
Keywords: Coopetencia; Estrategia; Competitividad